Antiparasitic activity of Colombian Amazon palm extracts against Giardia lamblia trophozoites: insights into cellular death mechanisms - García-Bustos, Juan Javier; Luna Pizarro, Gabriel; Patolsky, Rocío G.; Joray, Mariana Belén; Villalba-Vizcaino, Vivian; Galeano, Paula; Espitia-Almeida, Fabián; Correa Múnera, Marco; Ozturk, Mehmet; Rópolo, Andrea S.; Feliziani, Constanza; Touz, María Carolina; et al. (Frontiers in Microbiology, 2025)
IntroductionColombian plants have a long history of use in traditional medicine and ethnopharmacology, particularly for treating stomach pain, digestive issues, diarrhea, and other gastrointestinal disorders. Recent studies have renewed interest in their potential therapeutic properties.MethodsThis study evaluated the giardicidal activity of 15 crude plant extracts native to the Colombian Amazon against Giardia lamblia (genotype A, strain WB/1267). The MTT colorimetric assay was used to determine the effectiveness of these extracts at a concentration of 500 μg/mL. Extracts showing significant activity were further analyzed to determine their half-maximal inhibitory concentration (IC50). The cell death mechanisms of Attalea butyracea were studied using flow cytometry, confocal microscopy, and transmission electron microscopy (TEM).ResultsAmong the tested extracts, the Attalea butyracea fruit extract (P-2) exhibited the highest activity against WB/1267 (IC50 = 62.10 ± 6.57 μg/mL) and demonstrated giardicidal activity against GS/M (IC50 = 100.90 ± 3.40 μg/mL, genotype B) human infecting strains. These results prompted a detailed investigation into its mechanism of action using the WB/1267 strain as a model. At its IC50 concentration, P-2 primarily exerted its antiproliferative effect by induction of early apoptosis. A notable increase in late apoptosis and necrosis was observed at 2xIC50. Immunofluorescence assay (IFA) and confocal microscopy revealed chromatin condensation in treated trophozoites, while flow cytometry indicated G1/S cell cycle arrest. Furthermore, exposure to P-2 led to oxidative stress, evidenced by a significant increase in reactive oxygen species (ROS). The extract’s ability to disrupt various structural components of the parasite was confirmed through IFA and transmission electron microscopy. Interestingly, the P-2 extract effectively synergized with the first-line drug metronidazole against Giardia WB/1267 trophozoites.DiscussionThese findings underscore the therapeutic potential of Colombian plant extracts in treating giardiasis, particularly highlighting the novel giardicidal activity of Attalea butyracea fruit extract and its promise for further therapeutic development.